Perbandingan Hukum Tentang Pelecehan Seksual Terhadap Hewan Dengan Kuhp Indonesia Dan Kuhp Laos Criminal Code - Sekar Langit Jatu Pamungkas; Kuswardani Kuswardani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The Criminal Code (KUHP), which is a legacy of the Dutch colonial government, is nolonger relevant to changes and developments in society, especially if it is related to thediversity of types of sexual harassment as deviant sexual behavior which no longer makesfellow humans victims but has extended to a number of animal species. A specialcomparison is needed to find out the legal arrangements regarding sexual harassment ofanimals in order to find out whether Indonesia's legal system is better or worse. Laos isone of Indonesia's neighboring countries which is within the scope of the Southeast Asiaregion where the legal system used is also different and can be used as an appropriatecomparison to know in this study. So that it can be compared with each other whichcriminal law system is better in achieving justice as one of the goals of implementing alaw. The research method used in this research is the normative juridical law researchmethod. The results of the research show that the provisions of the criminal law rules ineach KUHP which are enforced as a source of criminal law for the Indonesian state andcriminal regulations in Laos as a comparison, it is known that in their application, bothThe applicable criminal law system does not clearly and specifically regulate sexualharassment behavior against animals.